PERILAKU KONSUMEN PADA PEMBELIAN BERAS BERMERK DI KABUPATEN JEMBER DAN FAKTOR YANG MEMPENGARUHINYA - Joni Murti Mulyo Aji; Agung Widodo (University of Jember, 2010)
This study was carried out to (1) seek to identify underlying factors influencing consumers’ decision to purchase branded packaged-rice; (2) understand whether packaging and brand are important factors influencing consumers’ decision t purchase packed-rice; (3) analyze consumers’ perception toward the function of brand in a packed-rice; and (4) seek to identify correlation between the level of income as well as education of consumers and their response to brand-factor on their decision to purchase a branded packaged-rice. The results of analysis show that brand and packaging were amongst important factors influencing consumer behavior on purchasing packed rice. Based on their importance, factors influencing consumer behavior on purchasing branded packaged-rice respectively were perceived quality; price; brand; purchasing place; source of information (reference); rice physical quality; product packaging; and promotion. Consumers mostly agree that brand is associated with several positive dimension of their perception. According to consumers, the dimensions associated with brand-factor respectively were product aesthetics, product performance, consumer satisfaction, product hygiene, product reliability and availability of the product. No correlation was found between the consumers’ level of income and their decision to purchase branded packaged-rice, but significant correlation was found for consumers’ level of education. This indicates that level of education potentially can be utilized to segment the branded packaged-rice market.Keywords: Rice, Consumer behaviour, Brand, Labelling